Police legitimacy and resident cooperation in crime hotspots: effects of victimisation risk and collective efficacy - Kochel, Tammy Rinehart (Policing and society, 2018)
This study focuses on police legitimacy and cooperation in high-crime neighbourhoods. Residents’ perceptions of victimisation risk and reduced collective efficacy are investigated as potential threats that may promote police legitimacy and cooperation. An integrated model applying systems justification theory, along with the instrumental and process models, provides potential mechanisms for understanding legitimacy and cooperation in crime hot spots. The multi-level regression analysis uses 947 surveys conducted in 71 crime hot spots. Results demonstrate the value of diffuse support for police and uphold the procedural justice and instrumental models of legitimacy in high-crime contexts. Results also support that risk and collective efficacy affect views. Findings point to the importance of how perceptions about context may foster a perceived dependence on police and, through this mechanism, promote cooperation. Results point to the value of further investigating risk, parochialism, and other aspects of context on police legitimacy and cooperation in future research.